Negative Transfer of Mother Tongue in Chinese-English Translation: A Case Study of Fortress Besieged and Memories of Peking: South Side Stories - Chen, Yanqiao (Transactions on Social Science, Education and Humanities Research, 2024)
In the field of negative language transfer, most studies have focused on students’ daily translation exercises, with relatively fewer investigations into literary translation. However, this paper aims to analyze the phenomenon of negative language transfer in Chinese-English translation, mainly focusing on its impact on tense expression and connection methods. Through analysis of examples from literary works (Fortress Besieged and Memories of Peking: South Side Stories), the essay demonstrates how linguistic features unique to Chinese, such as reliance on time adverbials and omission of connectives, can lead to errors in English translation due to negative transfer. The research also highlights the importance of linguistic proficiency, cultural understanding, and awareness of linguistic disparities in facilitating accurate and culturally appropriate translations and gives some related suggestions for better translation. This paper addresses the gap that exists in the negative language transfer field by carefully analyzing literary translation, contributing to a more comprehensive understanding of negative language transfer in translation practices.